Nacional Coordenation of Quilombos’s articulation: social actors and the capital forms - Barcellos da Silva Martins, Hélen (Revista Desenvolvimento Social, 2020)
The National Coordination of Quilombos‘s Articulation - CONAQ seeks to represent the Brazilian Quilombos‘s Communities in institutional and non-institutional spaces in order to obtain government recognition and titling of lands traditionally occupied, formulate and advocate the implementation of public policies applicable to these territories, and thus improve the quality of life of populations. Interests us observe how the birth process, organization and institutionalization of this entity and the political activism of leaders, they emerged from the political leadership of this organization. It is believed that these leaders, in the exercise of its militancy, accumulate capital (we use as theoretical and methodological framework based on the work of Pierre Bourdieu, 1986, in which he describes "The forms of capital") over time, allowing them know governmental institutional dynamics, prepare draft capita resources, learn the language needed to understand the processes and politician, gestures and persuasion in meetings among other accumulations. Thus, political action and obtaining social, cultural and political capital to provide access to information and put them in focus, allowing an increase in their level of school / academic training, commissioned performance in public office and other driving production and reproduction of life.